Social Media's Role in Creating New Fashion Trends - Putri Marganing Utami; Anita Volintia Dewi (Utan Kayu Publishing, 2024)
The rise of social media has significantly transformed the fashion industry, serving as a catalyst for the creation and dissemination of new fashion trends. Platforms like Instagram, TikTok, and Pinterest have become pivotal in shaping consumer preferences, offering instant access to global fashion inspirations. This study explores how social media influences fashion trends, examining the interplay between influencers, brands, and consumers. Social media allows for real-time interaction and feedback, enabling trends to emerge swiftly and organically. Influencers play a crucial role by curating and endorsing styles, while brands leverage these platforms to engage with their audience and adapt to evolving tastes. Furthermore, user-generated content contributes to the democratization of fashion, allowing everyday users to impact trends. This dynamic environment fosters innovation and diversity in fashion, breaking down traditional barriers and creating a more inclusive industry. By analyzing various case studies and current trends, this research highlights the mechanisms through which social media shapes fashion trends, emphasizing its role in trend creation, marketing strategies, and consumer behavior. The findings underscore the importance of social media as an indispensable tool for fashion industry stakeholders aiming to stay relevant and competitive in a rapidly changing market.